Soil carbon sequestration by root exudates - Panchal, Poonam; Preece, Catherine; Peñuelas, Josep; Giri, Jitender (Trends in plant science, 2022)
Root exudates are well-known ‘labile’ sources of soil carbon that can prime microbial activity. Recent investigations suggest that the stability of labile carbon inputs in soil mostly depends upon the physical, chemical, and biological properties of the surroundings. Here, we propose that, in some ecosystems, such as forests and grasslands, root exudates can function as a source of soil organic carbon (SOC) that can be stabilized through various mechanisms leading to long-term sequestration. Increasing soil carbon sequestration is important for capturing atmospheric CO2 and combating climate change issues. Thus, there is an urgent need to preserve existing ecosystems and to adopt strategies such as afforestation, reforestation, and establishment of artificial grasslands to foster carbon sequestration through higher root exudate inputs in the soil. Soil and plants are pivotal to the processes important for maintaining the integrity of biogeochemical cycles, such as the carbon cycle. Over the past few decades, anthropogenic activities have disturbed the atmospheric carbon cycle, leading to severe CO2 emissions into the atmosphere.Soil carbon sequestration by plant root exudates is an important means for net removal of CO2 content from the atmosphere.The rhizosphere environment in natural ecosystems, such as forests and grasslands, can help to stabilize root exudates in soil, while conditions in croplands do not appear favorable to stabilize root exudates as a soil organic carbon (SOC) source.Thus, preserving forests and grasslands with plant species secreting a high amount of carbon compounds might increase the SOC content in the soil of these ecosystems.